Marés, memórias e território: etnociência na comunidade pesqueira de Emboaca, litoral oeste do Ceará - Melo, Brenda Rozendo (2021)
Artisanal fishing activities are perceived as a cultural tradition and, in addition to being essential sources of income and subsistence for the populations, their importance transcends the local commerce of the communities, reaching 70% or more in the North and Northeast regions of Brazil. However, the idea of development based on the unrestrained growth of an economic model that uses natural elements in an unsustainable way, excludes the involvement of social, ecological and spiritual issues, generating socio-environmental conflicts that involve tensions over time, place and the way in which the environment is used. In this context, ethnoscientific research that understands the need to conserve the diversity of cultures in order to preserve the world's biodiversity and vice versa, configure alternatives contrary to this logic of capitalist development. Thus, this research aims, through the use of ethnographic methods that cross socio-cultural and natural elements, to understand and record the historical and daily relations between the fishing community of Emboaca (Trairi/CE) and the environment in which it is inserted, valuing local knowledge and customs in addition to meeting some of their demands, generating instruments for participatory management and defense of the territory. Therefore, this study has a qualitative character, whose construction was defined in dialogue with authors and social authors. The oral history of life and thematic methods was used – incorporating the “snowball” technique – for historical contextualization from the narratives of elder community members, in addition to the use of participant observation technique. In addition, social cartography workshops associated with guided tours were carried out in order to prepare the domain map of the territory by the Emboaca community. Thus, it was also possible to describe the environment with emicist and ethicist approaches. The records of stories told about the occupation of the territory by the community, the organization of the social space and the relationships built between people and the coastal environment, expressed both the affection of these people for the place, as well as knowledge passed from generation to generation, which goes through constant transformation, developing its adaptations based on knowledge and techniques originated through the observation and analysis of natural phenomena according to its needs. Social cartography generated important contributions to the articulation of the community, not only for the results, but for the entire process of collective construction, which even boosted struggles for community territorial rights. It is hoped that this support for social protagonism in community management has positively encouraged the community in facing environmental conflicts, strengthening autonomy in the search for good living.